Analisis SWOT Strategi Peningkatan Pelayanan Transportasi PT Kereta Api Indonesia (Persero) - Daeana Irawati; Dexi Triadinda; Dini Yani (Journal of Business and Economics Research (JBE), 2022)
The purpose of this study is to determine the service improvement strategy that can be applied by PT Kereta Api Indonesia (Persero) DAOP 2 Bandung. Service is an important point in especially business in the service sector, and in service research the problems that occur are improvement strategies. By using SWOT analysis, interview data was processed using the IFE (Internal Factor Evaluation) and EFE (External Factor Evaluation) Matrix. To describe the factors of strength and weakness using IFE while opportunities and threats using EFE. From the results of Strength and Opportunities (SO) of 4.56, Strength and Threats (ST) of 3.65, Weaknesses and Opportunities (WO) of 4.29, Weaknesses and Threats of 3.38. The combination of the highest alternative strategy and being in quadrant I, namely SO, is expected to have strength and can implement opportunities to improve existing services for better services in the future.